Effects of competition and ownership on the simultaneous relationship between bank risk and capital: Evidence from an emerging economy of Bangladesh. - Changjun Zheng; Md Mohiuddin Chowdhury; Anupam Das Gupta; Md Nazmul Islam (PLoS ONE)
This study aims to investigate the simultaneous relationship between bank risk and capital, specifically examining how competition and ownership jointly influence this relationship. We employed the two-step system generalized method of moments to address concerns regarding endogeneity and unobserved heteroscedasticity. Based on data from 44 commercial banks in Bangladesh from 2010 to 2021, our findings reveal several key insights: (I) There is a significant non-linear bidirectional relationship between bank risk and capital: capital exhibits a U-shaped effect on risk, while risk has a non-linear negative impact on capital; (II) in highly contested markets, banks hold higher levels of capital, and heightened competition reduces the risk appetite of commercial banks; while less competition has the opposite effect; (III) private and Islamic commercial banks are more risk-averse than state-owned and conventional ones, and (IV) Private and Islamic banks with strong capital positions in a competitive market can better manage risks than state-owned and conventional banks. However, maintaining higher capital ratios in competitive environments is more challenging for state-owned and Islamic banks than private-owned and conventional commercial banks. These results align with the moral hazard hypothesis, competition fragility hypothesis, and the political view of state ownership. Significant insights from the study will fuel the regulators in shaping policies and regulations surrounding emerging countries like Bangladesh, particularly regarding risk, capital, competition, and ownership policies.